A Qualitative Study on Perceptions of the Drill Method in Learning Vocabulary: Arabic and English Language - Safrodin, Muhamad; Falah, Ahmad Thoriqul; Eseadi, Chiedu (Journal of Educational Management and Strategy, 2024)
This study explores the perceptions of students and teachers regarding the drill method for vocabulary acquisition in Arabic and English. Conducted at Mambaus Sholihin 9 Islamic Boarding School in Blitar, the research involved 41 intermediate-level students and five teachers who regularly used the drill method in their instruction. Using a qualitative phenomenological approach, data were collected through semi-structured interviews and focus group discussions (FGDs), then analyzed using thematic analysis. The findings highlight that the drill method is effective in enhancing vocabulary retention for both Arabic and English, with 32 out of 41 students reporting improved recall. Teachers also emphasized its value in reinforcing vocabulary patterns, particularly for Arabics root-based morphology. However, challenges such as monotony and varying student proficiency levels were identified, with 9 students citing difficulty maintaining focus during repetitive drills. Language-specific differences were noted, with Arabic benefiting from pattern-based drills, while English required more contextualized examples to address nuances in usage. This study recommends integrating creative variations such as games, group activities, and contextual sentences to maintain engagement. Differentiated drills and adaptations to the structural characteristics of each language are suggested to enhance bilingual vocabulary acquisition. These findings contribute to the development of effective vocabulary teaching strategies for Arabic and English in bilingual educational settings.